(3GdCOH aj QLHs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdcGFfGJ Ydi gjFGJ eJHGjfGJ CeG HYO ajbhd Cf Gddg SHMGfg hJYGdi bGd (B" (3Ef YOI GdTghQ YfO Gddg EKfG YTQ TgQkG ai cJGH Gddg jhe Ndb GdSehGJ hGdCQV efgG (B" s
(3BNQgG (B:s
(3bjd cGf ajgG eYQGL SjO GdCfHjGA Edi GdSehGJ GdYdi hOfhg Edi ebGe bhSjf Ch COfi hgPG hLg JNUjU Cgd ecI ddRjGQI HTgQ QLH GdCUe hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs